Tackling the Threat of Rabies Reintroduction in Europe - Vega, Santiago; Lorenzo-Rebenaque, Laura; Marin, Clara; Domingo, Rosana; Fariñas, Fernando (Frontiers in Veterinary Science, 2021)
Rabies is one of the oldest, most important zoonoses worldwide due to its extreme and inevitably lethal nature, causing one death every 9 min worldwide. Recent reports have demonstrated that the Lyssavirus continues more alive than ever, despite the control carried out against the virus throughout Europe. In this context, this work reviews the main immunological implications, transmission risk factors and current prevention measures for virus control in Europe, and especially in Spain.